Vitamin C supplementation and athletic performance: a review - Rogers, D. R.; Lawlor, D. J.; Moeller, J. L. (Current Sports Medicine Reports, 2023)
Many athletes utilize high-dose vitamin C supplementation to optimize athletic performance. A review of research over the past 10 years on the use of vitamin C and athletic performance show mixed results. Fourteen randomized control trials were reviewed. In most studies, vitamin C was used with at least one additional supplement, usually vitamin E. Three studies showed positive outcomes associated with decreased markers of muscle damage after intense exercise with some form of vitamin C supplementation. The remaining 11 articles showed either neutral or negative effects of high dose vitamin C supplementation on muscle damage, physical performance, perceived muscle soreness, and/or adaptations to training. Based on a lack of consistent data and potential for blunted physiologic adaptations to training, long-term high-dosage supplementation with vitamin C is not recommended. Athletes should obtain antioxidants through a nutrient-rich diet instead of through supplement use.